Climate change in Asia and the Pacific : how can countries adapt? - Anbumozhi, Venkatachalam; Asian Development Bank Institute (New Delhi, India ; Thousand Oaks, Calif. : Sage, 2012)
Papers presented at two ADBI workshops on Climate change adaptation, held at Tokyo in 2009 and Colombo in 2010.
"This book is based on papers presented at two ADBI [Asian Development Bank Institute] workshops on climate change adaptation held in Tokyo, Japan, in 2009, and Colombo, Sri Lanka, in 2010"--Foreword.
Includes bibliographical references and index.
Keywords: Climatic changes -- Risk management -- Asia; Climatic changes -- Risk management -- Pacific Area; Climatic changes -- Asia; Climatic changes -- Pacific Area; Climatic changes -- Government policy -- Asia; Climatic changes -- Government policy -- Pacific Area